Study on the method of colour image noise reduction based on optimal channel‐processing. Issue 9 (1st September 2018) - Wang, Yutan; Dai, Yingpeng; Liu, Xiangnan; Liu, Bohan; Guo, Xiaoyun
Abstract : The methods of the image noise reduction based on optimal channel‐processing to enhance image quality are studied. According to different noise with the different ratio in colour components, different noise reduction technologies are used for noise reduction. Then the optimal algorithm is automatically selected as the ultimate way of noise reduction in each channel. For the purpose of optimal noise reduction effect, this study presents a method of combining the quadratic optimisation with the variable window processing. The quadratic optimisation provides a good environment for noise reduction by decreasing complexity of mixed noise and the variable window processing calibrates the image smoothing result. Compared with mean filtering, median filtering and adaptive filtering, the image quality processed by the proposed algorithm is generally improved by >2 dB.